Computational number theory and modern cryptography - Yan, Song Y. (2013)
"The only book to provide a unified view of the interplay between computationalnumber theory and cryptographyComputational number theory and modern cryptography are two of the most important and fundamental research fields in information security. There are many textbooks on computational number theory or cryptography. However, textbooks integrating both topics are rare. This book not only introduces the basic concepts and results in the two fields, but also introduces many advanced topics. Mathematical ideas are presented first, thereupon treating cryptography as an immediate application of the mathematical ideas. The author covers topics from number theory which are relevant for applications in public-key cryptography. The most popular public-key cryptosystems are based on difficult computational problems, such as factorization of large positive integers and the discrete logarithm problem in finite fields or on elliptic curves over finite fields. The book also covers modern topics, such as coding and lattice based cryptography, which are relevant for so-called post-quantum cryptography. The author goes over the basics in the first six chapters, followed by application to the most common cryptographic algorithms in the following three chapters. Finally areas of current research are touched in the last three chapters. Serious mathematical problems behind these applications will be explained at the level accessible to computer scientists and engineers. Makes deep mathematical problems accessible to computer scientists and engineers Based on classroom tested materials used in the US, UK and China Exercises included in every chapter Instructor resources available on the book's Companion Website "--
"This book not only introduces the basic concepts and results in the two fields, but also introduces many advanced topics"--
Includes bibliographical references and index.
Keywords: Data encryption (Computer science); Number theory -- Data processing; COMPUTERS / Security / Cryptography